Before Daybreak : "After the Race" and the Origins of Joyce's Art - Owens, Cóilín (Book collections on Project MUSE., 2012)
A close examination of the story "After the Race," which originally appeared in Joyce's Dubliners. This book argues that the story represents a microcosm of some of the issues most central to Joyce scholarship: evolution as an artist, the Catholic Church, and nostalgia for a rapidly changing Ireland.